How to Supervise Senior Design Projects - , Maruf A. Aminu; , Oyediran Olufemi (Archives of Current Research International, 2019)
Senior design projects for engineering students typically integrate various components of the curriculum to apply the basic sciences, mathematics and engineering sciences in realizing physical systems which solve real problems or make life more livable. The process of realizing senior design projects requires supervision from academics. Majority of young academics may not have sufficient experience to adequately understand the dynamics of this process, from conception to realization. The gap in experience as well as deficit of literary resources on practical steps for project supervision impacts negatively on the overall success of the student as well as the project. This paper presents, in practical steps, the general procedures for supervision of senior design projects in electrical and electronics engineering for optimal realization of projects. The paper discusses project supervision from conception to manuscript development, taking into consideration some of the potential challenges typically encountered. Finally, it presents typical inadequate and adequate titles as well as abstracts for a circuit.